A report on practicum conducted at Calatagan aquaculture system and Oliva fishfarm Clalatagan, Batangas. - Melgar, Maria Rosena (College of Fisheries, University of the Philippines, 1991)
The study of aquaculture, in all aspects, requires knowledge both learned and acquired. The information gathered from our studies are utilized to explain the cause and effect that alters normal pond operation and management. This in addition increases the acquired knowledge gained from such experience. There is a need to see more than graphs, slides and text to become successful technicians and aquaculturists. Field experience is the knowledge of what is really happening in real fish farm. Our professors real and not theoretically give the problems. It is where probable guesses will not cause red mark on our papers but real money. As much as possible, we cannot afford to commit mistakes. As future technicians, we will be placed the burden of making such decisions. In doing these, we must remember what we have learned from our professors and our books. Now we must learn aquaculture n reality in the field. Thus, the need for practicum. And may all the things we have gone through, the knowledge, both learned and acquired, be sufficient enough for the need of the industry. That we may able to do our little share in helping our country achieve its goal of self-sufficiency.